The Nexus between FDI, Per Capita Income, Energy Consumption, Trade Openness, and Carbon Dioxide Emissions: Panel Data Analysis of ASEAN Plus Six - Luthfiana Rahma; Rudy Firmansyah; Mohamad D. Revindo (Research Center for Regional Resources-Indonesian Institute of Sciences (P2SDR-LIPI), 2020)
ASEAN and ASEAN Plus countries’ commitment in following the Paris Agreement requires them to utilize trade and investment to balance economic growth and improve environment quality. Using observational data from eleven ASEAN Plus countries from 1979–2018, this study aims to assess how income, energy consumption, FDI, and trade openness jointly cause CO2 emissions in ASEAN Plus countries using panel data estimates. This research proves the existence of the Inverted-U Environmental Kuznets Curve phenomenon in ASEAN Plus countries. In addition, a significant increase in energy consumption explains the increase in CO2 emissions levels in this region. FDI inflows have been found to have a negative relationship with the level of CO2 emissions. Meanwhile, trade openness has been found to positively influence the level of CO2 emissions. This FDI and trade relationship with CO2 emissions shows the need for a new harmonization of a more environmental-friendly integrated production system in the region.